Peningkatan Hasil Belajar Mata Pelajaran IPAS Melalui Model Problem Based Learning Pada Peserta Didik Kelas IV SDN Karangrejo 02 Semarang (psnppg, 2025)
Classroom action research aims to improve learning outcomes in improving the learning outcomes of class IV students at SDN Karangrejo 02 Semarang through the PBL (Problem Based Learning). The PBL Learning Model is an approach that emphasizes solving real problems in contexts that are relevant to students' daily lives. This research was conducted by involving 16 first grade students at SDN Karangrejo 02 Semarang as research subjects. Each cycle consists of one learning meeting. The results showed that the percentage of completeness cycle I and cycle II. namely in cycle 1 44% completed with average value of 60. In cycle II 64% completed with an average value of 72.Keywords : Classroom Action Research, PBL Learning Model, Student Learning Outcomes, Basic EducationClassroom action research aims to improve learning outcomes in improving the learning outcomes of class IV students at SDN Karangrejo 02 Semarang through the PBL (Problem Based Learning). The PBL Learning Model is an approach that emphasizes solving real problems in contexts that are relevant to students' daily lives. This research was conducted by involving 16 first grade students at SDN Karangrejo 02 Semarang as research subjects. Classroom action research was conducted in two cycles, with each cycle consisting of planning, implementing, observing, and reflecting. Each cycle consists of one learning meeting. The results showed that the percentage of completeness cycle I and cycle II. namely in cycle 1 44% completed with average value of 60. In cycle II 64% completed with an average value of 72.
Keywords: : Classroom Action Research; PBL Learning Model, Student Learning Outcomes; Basic Education